Determinación de los riesgos ergonómicos y su incidencia en la salud de los trabajadores del área de empaque en la empresa CEDAL. - Ávila Guanoluisa, Jorge Edmundo (2019)
The present investigation is based on the principles of occupational safety and health, mainly on the comfort of the employee in his work space and it is aimed at determining the ergonomic risks, basically those that affect the work performance in the packing area of the “CEDAL” company with the purpose of knowing the incidence in the health of the workers. The objective of the project is to identify the tasks that contradict ergonomic risks that affect personnel and determine the level of incidence in the health of personnel through a bipolar assessment of discomfort. The last one allows determining the level of musculoskeletal disorders of a person due to overexertion in his or her activities. The research project will have an economic and social impact on the plant since the ergonomic risks derive from musculoskeletal injuries and discomforts, that cause work absenteeism in a certain area due to repetitive movements, load lifting and inadequate work postures. , as well as low productivity in the personnel. Through the implementation of the following engineering controls: at the source, in the transmission medium and in the worker, a manual of preventive measures is planned to mitigate the injuries derived from the ergonomic risks to which the personnel of the packaging area is exposed, protecting their safety and health in their workplace. As a final result of the risk study analysis, work techniques and methods will be proposed. These mechanisms will allow to decrease the effect of the same in the workers’ health, such as: active pauses, organization and implementation of tools that reduce the physical effort of the personnel and, provision of personal protection equipment according to the activity.